The mediating role of school effectiveness in the relationship between transformational leadership and workplace exclusion - Kandemir, Ayhan (Frontiers in Psychology, 2024)
The purpose of this study is to reveal the mediating role of school effectiveness in the relationship between transformational leadership and workplace exclusion. The sample of the study consisted of 410 teachers working in primary, secondary and high schools in Bolu/Turkiye province center in the 2023-2024 academic year. Correlational design was used in the study and path analysis was used to reveal the predictive relationships between variables. As a result of the study, it was seen that the hypotheses put forward in line with the model put forward were confirmed. In this context, it was concluded that transformational leadership has a significant positive effect on school effectiveness (Hypothesis 1), school effectiveness has a significant negative effect on workplace exclusion (Hypothesis 2), transformational leadership has a significant negative effect on workplace exclusion (Hypothesis 3) and finally school effectiveness has a mediating role in the effect of transformational leadership on workplace exclusion (Hypothesis 4). In the context of the results, suggestions were made such as providing in-service courses for school administrators on transformational leadership and school effectiveness, preventing exclusion at work by giving teachers the opportunity to develop themselves and participate in the decisions taken.